2014
DOI: 10.2147/copd.s74298
|View full text |Cite
|
Sign up to set email alerts
|

Use of time in people with chronic obstructive pulmonary disease – a systematic review

Abstract: “Physical inactivity” and “sedentary lifestyles” are phrases often used when describing lifestyles of people with chronic obstructive pulmonary disease (COPD). Evidence suggests activity types, independent of energy expenditure, influence health outcomes, so understanding patterns of time use is important, particularly in chronic disease. We aimed to identify reports of time use in people with COPD. Predefined search strategies were used with six electronic databases to identify individual activity reports (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 47 publications
4
21
0
1
Order By: Relevance
“…This was not surprising, since there was no difference in lying time/d between survivors and non-survivors (Table 1). A recent review about the use of time in daily life by subjects with COPD 14 found a median of time spent lying of 88 min/d, therefore very close to our cutoff point of 80 min/d. Perhaps a discriminative cutoff point for lying time was not detected in the present sample.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This was not surprising, since there was no difference in lying time/d between survivors and non-survivors (Table 1). A recent review about the use of time in daily life by subjects with COPD 14 found a median of time spent lying of 88 min/d, therefore very close to our cutoff point of 80 min/d. Perhaps a discriminative cutoff point for lying time was not detected in the present sample.…”
Section: Discussionsupporting
confidence: 79%
“…12 Patients with COPD typically do very little activity at moderate or vigorous intensities, 7,13 and sedentary behavior is predominant in their daily lives. 7,14 Previous studies have shown the association between physical activity profile and mortality among many other outcomes in these subjects. 1,[15][16][17] However, up to this moment, there is no study on COPD that has investigated the association between mortality and variables of sedentary behavior (instead of variables of physical activity), according to the above-mentioned definitions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings that less healthy participants in our study were more sedentary and did less even light physical activity are largely consistent with studies focused on disease populations. Such studies have similarly found that less healthy participants spent less time doing chores and more time watching television than healthy counterparts [10,31].…”
Section: Key Findingsmentioning
confidence: 91%
“…Healthcare and professional support Clinical support: Healthcare staff who care, feeling well looked after, having treatments explained (11,9) Good access: Being able to see a doctor or nurse when necessary (9,7)…”
Section: What Is Working Well?mentioning
confidence: 99%
“…The right medication when needed, feeling empowered to use it (6,9) Feeling safe: Receiving support to feel safe (4,0) Other themes reflected frustrations including I'm confused by conflicting advice from different people; I'm angry when there are errors (I felt angry when a nurse made a mistake-it made the results wrong and I was given the wrong information. They didn't say sorry); I feel rushed during appointments; I was ill-informed (I would have liked my condition explained more when I was diagnosed.)…”
Section: What Is Working Well?mentioning
confidence: 99%